Development of creativity-based learner worksheets in science subjects at elementary school - Sari, Alvi Dwi Kartika; Anas, Nirwana (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
Creativity is a very important skill to have, without creativity a person will not be able to adapt to the developments that occur in the current era of globalization. The ability to think creatively is very important for students because through creative thinking, students are expected to understand, manage, and solve the problems they face. The creativity that students have can be a skill they have to face every opportunity and difficulty they will face. The method applied in this research is Research and Development (R&D). The development of this LKPD refers to the development model proposed by Robert Maribe Brach with the ADDIE approach. ADDIE stands for Analysis, Design, Development, Implementation, and Evaluation. Learning by using LKPD based on creativity is effective and can be used in the learning process in grade IV elementary school students. The feasibility of learning media has been reviewed by subject matter experts, media experts, and trials on grade IV elementary school students. Validation assessed by material experts and media experts, shows that creativity-based LKPD is included in valid criteria and is suitable for use as teaching materials for teachers and students. It can be concluded that creativity-based LKPD is effective for science learning on photosynthesis material. For future researchers, they can develop better and better Learner Worksheets, besides based on creativity, LKPD can be developed based on other 4C skills, such as collaboration, communication, critical thinking, innovation.